Asian LNG market changes under low oil prices: prospects for trading hubs and a new price index. Issue 3 (4th May 2017) - Kim, Younkyoo
Abstract: Presented is an analysis of the changes in the North-East Asian energy landscape as a result of the decline in global oil prices. The end of February 2016 saw the first exports of liquefied natural gas (LNG) from the U.S. mainland when major shale gas company Cheniere Energy's first LNG cargo left the Sabine Pass terminal in Texas. There are expectations that the beginning of U.S. LNG exports may trigger flexible trading. To the year 2020, U.S. LNG exports to North-East Asia will be increased. North-East Asia needs to continue its effort to promote regional cooperation and co-prosperity by building a North-East Asian gas trading hub. Russia will seek to keep U.S. LNG in check through price negotiations. The evolution of an Asian gas hub will be to a great extent influenced by how Russia and China will reconsider their energy strategies.